THE SIGNIFICANCE OF USING INNOVATIVE TECHNOLOGIES IN TEACHING ENGLISH TO STUDENTS OF ARCHITECTURAL UNIVERSITIES - Adashevna, Fozilova Makhina (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2023)
This article analyzes the significance of interactive methods in the process of teaching a foreign language, in particular English, and their effective application in teaching students of architectural educational institutions. We also consider and study certain types of interactive methods that contribute to the development of communication skills, logical thinking and other types of intellectual activity.